2007
DOI: 10.2460/javma.230.9.1340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transfixation casting for treatment of third metacarpal, third metatarsal, and phalangeal fractures in horses: 37 cases (1994–2004)

Abstract: Results indicated that transfixation casting can be successful in managing fractures distal to the carpus or tarsus in horses. This technique is most suitable for comminuted fractures of the proximal phalanx but can be used for third metacarpal, third metatarsal, or middle phalanx fractures, with or without internal fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
83
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 16 publications
(37 reference statements)
5
83
0
3
Order By: Relevance
“…Complications of surgical treatment of third metacarpal fractures can be rather common (19 %) and involve local problems like fragmentation of drill bits, osteomyelitis, disturbed fracture union, catastrophic failure of the cannon bone or local infections as well as more generalised complications like laminitis and colitis (McClure et al 1998, Lescun et al 2007). Furthermore, recurrence of the fracture at the same site does occur (Cervantes et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Complications of surgical treatment of third metacarpal fractures can be rather common (19 %) and involve local problems like fragmentation of drill bits, osteomyelitis, disturbed fracture union, catastrophic failure of the cannon bone or local infections as well as more generalised complications like laminitis and colitis (McClure et al 1998, Lescun et al 2007). Furthermore, recurrence of the fracture at the same site does occur (Cervantes et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…al. 1996, Leskun et al 2007, Nash and Nunamaker 2008, De Godoy et al 2009). Attempts to use an Ilizarov fixator in horses showed that the strength in this treatment is not sufficient (Cervantez et.…”
Section: Introductionmentioning
confidence: 99%
“…Em equinos, são utilizados para tratar fraturas de McIII, MtIII, multifragmentares, expostas ou com extensa lesão de tecidos moles (LESCUN et al, 2007 O plasma rico em plaquetas (PRP) concentra uma grande variedade de fatores de crescimento e aumenta a taxa de proliferação de vários tipos celulares, além de desempenhar um papel importante na síntese e remodelamento do tecido de reparação (GRIFFIN et al, 2009;CARMONA et al, 2011). Assim, o objetivo desta nota é relatar o caso de uma potra com fratura diafisária multifragmentar em cunha de MtIII, tratada com pinos transcorticais e gesso, associados à injeção local de PRP.…”
unclassified
“…Nas fraturas completas do Mc/MtIII em equinos jovens, recomenda-se o tratamento cirúrgico, com redução aberta e imobilização do foco com duas placas de compressão dinâmica que visam à reconstrução anatômica do osso (BISCHOFBERGER et al, 2009;LEVINE & RICHARDSON,2007). Porém, pela característica multifragmentar da fratura, optou-se pela imobilização com pinos transversais, sem a abordagem cirúrgica do foco, visando a minimizar lesões vasculares e aos tecidos moles adjacentes e diminuir o risco de contaminação bacteriana com consequente colonização do implante (LESCUN et al, 2007).…”
unclassified